A Copper Catalyst with a Cinchona‐Alkaloid‐Based Sulfonamide Ligand for Asymmetric Radical Oxytrifluoromethylation of Alkenyl Oximes. (25th May 2018) - Li, Xi‐Tao; Gu, Qiang‐Shuai; Dong, Xiao‐Yang; Meng, Xiang; Liu, Xin‐Yuan
Abstract: A copper‐catalyzed asymmetric radical oxytrifluoromethylation of alkenyl oxime and Togni's reagent has been successfully developed, thereby providing straightforward access to CF3 ‐containing isoxazolines bearing α‐tertiary stereocenters with excellent yield and enantioselectivity. The key to success is the rational design of cinchona‐alkaloid‐based sulfonamides as neutral/anionic hybrid ligands to effectively control the stereochemistry in copper‐catalyzed reactions involving free alkyl radical species. The utility of this method is illustrated by efficient transformation of the products into useful chiral CF3 ‐containing 1, 3‐aminoalcohols.